KEMAMPUAN MENELUSUR KATALOG DARING: HASIL PENGUJIAN KATALOG DARING PADA 10 PERPUSTAKAAN BESAR DI INDONESIA - Permadi, Agus (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
The study aims to find out whether important search techniques could be employed to find records in the ten online public access catalogs (OPACs) tested. The following search tests are conducted: (1) test to determine the fields used as access point to records, and the number of fields searched when a two-word syntax was used; (2) search using one to three charaters, one word, and English stopwords; (3) search using boolean AND, OR or NOT and their combinations; (4) phrase search; (5) truncation search; and (6) search using filters (e.g., language or year of publication) provided by the OPACs. Results of the tests were: (1) access to records was available through title, author, subject, series, and note in eight systems; (2) a two-word syntax was searched only in one field in all systems; (3) English words and syntaxes of one to three characters were searched in eight systems; (4) boolean operators AND, OR and NOT and their combinations could be used only in one system; (5) search employing filters could be performed in three systems. It was concluded that nine of the ten OPACs could not provide optimal access to records. The OPAC is the only access to library collections for those who search through the Internet; therefore, complete search tests of its search facilities are required before a system is released. Further research is needed to find efficient search test methods that could be used by the developers and librarians to prove that a search facility functions.